The usage of wim to enhance the acquisition of english language - Rathakrishnan, Mohan; Raman, Arumugam; Sarjit Singh, Manvender Kaur; Jocksee@ Jagdish S, Yashpaul Kaur A/P (Opción, 2019)
This study compares an independent study of students in an experimental mobile group (40 students) with a control group (40 students) from two Form Four classes. A mixed method of research design has been used in the study. The result shows that the performance of the experimental group is much greater compared to the performance of control. Mobil learning could make students feel more comfortable in learning the English language and communicate without seeking a teacher’s support and guidance in completing any task given to them by using mobile learning related to their studies matter.